Plant-derived extracellular vesicles and nanoparticles: origins, functions, and applications - Alsaid, Faris; Davila, Brisa; He, Baoye (Frontiers in Bioengineering and Biotechnology, 2026)
Plant-derived extracellular vesicles (PDEVs) and plant-derived nanoparticles (PDNPs) are emerging plant-based nanomaterials with growing relevance in biotechnology, agriculture, and health. Although often grouped together, they arise from distinct origins: PDEVs are actively secreted vesicles with selective cargo loading, whereas PDNPs form during tissue disruption and reflect the lipid-metabolite composition of plant biomass. This review summarizes recent progress in distinguishing these systems, including advances in biogenesis, isolation, biomarkers, and functional characterization. We highlight mechanistic insights into PDEV-mediated cross-kingdom RNA communication in plant immunity and the strong translational potential of PDNPs in oral drug delivery, immunomodulation, and microbiome regulation. Remaining challenges include standardization, scalable purification, and deeper mechanistic clarity. By clarifying their differences and complementary strengths, this review outlines a foundation for developing reliable plant-derived nanovesicle technologies.